Molecular Docking and Pharmacokinetic Profiling of the Phytocompounds of Jatropha curcas as Antagonist for Salmonella typhi - Nayan M (International Journal of Cell Biology and Cellular Functions, 2023)
Background: Typhoid is an infection caused by the Gram-negative bacterium, Salmonella enterica serovar typhi. The study assessed the potential use of Jatropha curcas as a typhoid fever therapy alternative to traditional medications. The ability to uncover novel drug indications for currently available medications using in silico methods has increased thanks to the wealth of pharmacological and biological knowledge that is available. Objective: In this study, we assessed the potential inhibitory effects of phytocompounds from Jatropha curcas against five proteins of Salmonella typhi. Methods: Molecular docking was implemented to evaluate the efficacy of 93 phytocompounds from Jatropha curcas against the target proteins of Salmonella typhi. (Beta-lactamase, DNA Gyrase B, Lactate dehydrogenase, L-lactate dehydrogenase and Retinal dehydrogenase). PyRx, a Virtual Screening software was utilized for molecular docking which allowed the inspection of three-dimensional protein structures and the identification of potential binding sites. ADMET Lab 2.0 was used to evaluate the drug-likeness properties of the phytoconstituents. Results: On analysing the molecular docking results, 4-(P-Methoxyphenyl)-2-(4-phenyl-2-pyridyl)-6-(2-pyridyl)-pyridine, 2-Quinazolinamine, 3,4-dihydro-N,3-diphenyl-4-(phenylimino)-, alpha-Amyrin and Isovitexin exhibited the best binding affinity towards the five target proteins of Salmonella typhi. Conclusion: This study demonstrated that Jatropha curcas is a reliable source of potential phytotherapy for treating Typhoid.
Keywords: 2-Quinazolinamine; 3-diphenyl-4-(phenylimino)-; 4-(P-Methoxyphenyl)-2-(4-phenyl-2-pyridyl)-6-(2-pyridyl)-pyridine; 4-dihydro-N; ADMET; Beta-lactamase; DNA Gyrase B; L-lactate dehydrogenase and Retinal dehydrogenase; Lactate dehydrogenase; Typhoid; alpha-Amyrin and Isovitexin; binding affinity; molecular docking; phytocompounds